Buenas intenciones y práctica real. La expresión escrita en la asimilación de conceptos lingüísticos en bachillerato - Allué Villanueva, Consuelo (Huarte de San Juan. Filología y Didáctica de la Lengua, 2013)
With this work of presentation of our experiences with students of 1st «Bachiller» in language and literature classes, we hope to demonstrate how regular and systematic written expression’s works, raised directly related to the contents and concepts that we work, contribute to a greater and more genuine assimilation of the contents and concepts and to get a real development of the language skills (as well as others) to transform the declarative in procedural. As proof, support and exemplification of what we affirm, we introduce some texts of the students who serve as «balance of results», because through them we can see that students assimilate the concepts in question and that our methodology and process are effective.